Identification of Junior High School Students' Experiences in Using Question Card Media for Algebra Learning - Qomaria, Nur; Afifah, Ani; Manivannan, Rathish (Delta-Phi: Jurnal Pendidikan Matematika, 2025)
This study aims to explore junior high school students' experiences in using Question Card media in algebra learning. Using a qualitative approach, this study involved 26 students of grade VII B at SMP Darul Ulum 5 Rebalas as the main participants. Data were collected through classroom observations, interviews, and student response questionnaires to understand perceptions, engagement, and challenges faced during the learning process using Question Cards. The results showed that Question Card media was able to increase students' interest, attention, and engagement in algebra learning. Most students stated that using Question Cards made learning more interactive, enjoyable, and helped them understand abstract algebraic concepts. Data analysis showed that the level of student learning interest was in the high category (74.7%), with indicators of engagement and attention also showing high percentages. However, there were some students who still felt more comfortable with conventional methods, so further adaptation was needed. These findings confirm that Question Card media can be an innovative alternative in mathematics learning, especially algebra, to enhance students' learning experiences actively and meaningfully. This study recommends the development of similar media and training for teachers to optimize the use of interactive media in mathematics learning at the junior high school level.